1977
DOI: 10.1161/01.res.41.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Circus movement in rabbit atrial muscle as a mechanism of tachycardia. III. The "leading circle" concept: a new model of circus movement in cardiac tissue without the involvement of an anatomical obstacle.

Abstract: SUMMARY In small pieces of rabbit atrial myocardium, sustained periods of circus movement tachycardia were produced by the induction of a single properly timed premature impulse. By use of multiple intracellular and extracellular electrodes the spread of activation during the tachycardia could be analyzed accurately. Because in the present experiments there was no gross anatomical obstacle for the impulse to circulate around, we paid special attention to phenomena occurring in the center of the circus movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
369
0
13

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 989 publications
(395 citation statements)
references
References 14 publications
(17 reference statements)
11
369
0
13
Order By: Relevance
“…AF is generally considered to be maintained by multiple re-entrant wavelets of excitation that propagate in different directions around the atrial myocardium [26,27]. The maintenance of AF seems to depend on the presence of a sufficient number of small wavefronts while undergoing fractionation, collisions and coalescence over the atrial surface.…”
Section: Self-limited Vs Self-sustained Atrial Fibrillationmentioning
confidence: 99%
“…AF is generally considered to be maintained by multiple re-entrant wavelets of excitation that propagate in different directions around the atrial myocardium [26,27]. The maintenance of AF seems to depend on the presence of a sufficient number of small wavefronts while undergoing fractionation, collisions and coalescence over the atrial surface.…”
Section: Self-limited Vs Self-sustained Atrial Fibrillationmentioning
confidence: 99%
“…The fundamental mechanisms underlying AF are still debated, but regardless of the initiating event, there is broad consensus that AF is maintained by rapid focal activation or by re‐entrant wavelets of depolarization moving randomly across the atria 13, 14, 15. Flecainide is, because of its sodium channel blocking properties, classified as a class IC antiarrhythmic drug.…”
mentioning
confidence: 99%
“…In the ventricle, local reentry is considered to be the most probable mechanism for tachycardias (Josephson and Seides 1979) and local conduction delay was documented in canine heart (El-Sherif et al 1977) and in man (Josephson et al 1978). As for atrial tachycardias, Wydham et al (1980) suggested triggered activity to be one of the mechanisms, but reentry is also proposed (Allessie et al 1977;Pastelin et al 1978; Watson and Josephson 1980;Boineau et al 1980), and a conduction delay is shown to be a major predisposing factor for the development of atrial flutter (Leier et al 1978). In this report we observed peculiar split atrial activity which suggests some defects of conductivity in the atrium of a man with brady-tacky syndrome.…”
mentioning
confidence: 99%